Hubungan Sistem Kepercayaan dan Jenis Pekerjaan dengan Tingkat Partisipasi Nelayan dalam Upacara Adat Sedekah Laut - Febria Nur Endah Putri; Ahman Sya; Cahyadi Setiawan (Geography Education Study Program, Universitas Kanjuruhan Malang, 2024)
Sea alms are held as a form of community gratitude for the abundant sea products as well as gratitude for the safety provided by Allah SWT in carrying out activities as fishermen. The purpose of this study is to determine the level of belief of the fishing community in the sea alms ceremony, second is to determine the income level of fishermen in Gempolsewu Village, third is to determine the level of participation of fishermen in the sea alms ceremony in Gempolsewu Village and fourth is to determine the relationship of the belief system and type of work to the participation of fishermen in the sea alms ceremony in Gempolsewu Village, Rowosari District. This research utilizes mixed methods research and uses survey techniques for data collection. The results of this study state that the level of belief of the fishing community in the sea alms ceremony is in the high category, the income level of the fishing community is in the medium category, and for the level of fishermen's participation is in the high category. For the relationship between the belief system and type of work, there is no significant relationship between the two variables on the participation of fishermen in the sea alms ceremony in Gempolsewu Village, Rowosari District. The author recommends to further researchers to conduct further research on the relationship of other cultural elements of traditions in Indonesia.